Functional class of chronic heart failure and immunoinflammatory markers (IL-1β, IL-10) in patients with ischemic heart disease and type 2 diabetes - Наріжна, Анна Василівна; Риндіна, Наталія Геннадіївна; Narizhna, Anna; Ryndina, Natalia (ХНМУ, 2015)
The presence of type 2 diabetes in patients with chronic heart failure on a background of ischemic heart disease is characterized by an imbalance of cytokine system working, which manifests by high concentrations of proinflammatory IL-1β and low anti-inflammatory cytokine - IL-10.The attempts of balance work of immunoinflammatory markers are characterized by both – pro- and anti-inflammatory link high activity in patients with chronic heart failure without type 2 diabetes
Keywords: chronic heart failure; ischemic heart disease; type 2 diabetes; inflammatory; interleukines